High stereographic resolution texture and residual stress evaluation using time‐of‐flight neutron diffraction. Issue 3 (9th May 2018) - Xu, Pingguang; Harjo, Stefanus; Ojima, Mayumi; Suzuki, Hiroshi; Ito, Takayoshi; Gong, Wu; Vogel, Sven C.; Inoue, Junya; Tomota, Yo; Aizawa, Kazuya; Akita, Koichi
Abstract : The division of neutron detector panel regions has improved the precision of complex texture evaluation and appropriate sample rotation enhances the texture reliability in a limited neutron beam time. The TAKUMI instrument has achieved satisfactory texture precision for a limestone standard sample. The compressive rolling direction–transverse direction in‐plane stress field was quantitatively measured in martensite layers of a martensite–austenite multilayered steel, and this stress field was found to originate from the martensite transformation strain and the linear contraction misfit between austenite layers and newly transformed martensite layers. Abstract : Neutron diffraction texture measurements provide bulk averaged textures with excellent grain orientation statistics, even for large‐grained materials, owing to the probed volume being of the order of 1 cm 3 . Furthermore, crystallographic parameters and other valuable microstructure information such as phase fraction, coherent crystallite size, root‐mean‐square microstrain, macroscopic or intergranular strain and stress, etc. can be derived from neutron diffractograms. A procedure for combined high stereographic resolution texture and residual stress evaluation was established on the pulsed‐neutron‐source‐based engineering materials diffractometer TAKUMI at the Materials and Life Science Experimental Facility of the Japan Proton Accelerator Research Center, through division of the neutron detector panel regions. Pole figure evaluation of a limestone standard sample with a well known texture suggested that the precision obtained for texture measurement is comparable to that of the established neutron beamlines utilized for texture measurement, such as the HIPPO diffractometer at the Los Alamos Neutron Science Center (New Mexico, USA) and the D20 angle‐dispersive neutron diffractometer at the Institut Laue–Langevin (Grenoble, France). A high‐strength martensite–austenite multilayered steel was employed for further verification of the reliability of simultaneous Rietveld analysis of multiphase textures and macro stress tensors. By using a texture‐weighted geometric mean micromechanical (BulkPathGEO) model, a macro stress tensor analysis with a plane stress assumption showed a rolling direction–transverse direction (RD–TD) in‐plane compressive stress (about −330 MPa) in the martensite layers and an RD–TD in‐plane tensile stress (about 320 MPa) in the austenite layers. The phase stress partitioning was ascribed mainly to the additive effect of the volume expansion during martensite transformation and the linear contraction misfit between austenite layers and newly transformed martensite layers during the water quenching process.